Biologically oriented synthesis of medicines (BIODS) based on heterylpoxid 2,5- disubstituted 1,3,4-oxadiazoles (Part 1) - Yu. V. Karpenko; O. I. Panasenko; Ye. H. Knysh (Zaporozhye State Medical University, 2020)
At the present stage of development of medical chemistry, many basic synthetic approaches to the synthesis of 1,3,4-oxadiazole structures are known, which are focused mainly on the principles of combinatorial chemistry with a wide range of biological activity. The aim of the work was searching, systematizing, and generalizing literature sources for biologically oriented drug synthesis (BIODS) based on hetero derivatives of 2,5 disubstituted 1,3,4-oxadiazoles. Heterocyclic systems containing a 1,3,4-oxadiazole nucleus have a rich synthetic history and are characterized by a wide range of synthesis methods. The review article firstly summarizes the literature on the chemistry of hetero derivatives of 2,5 disubstituted 1,3,4-oxadiazoles as important synthetic substrates and precursors for biologically oriented synthesis. The most classical methods of obtaining, which are the intramolecular dehydration of 1,2-diacylhydrazines, the interaction of hydrazyl carboxylic acid hydrazides with carbon disulfide and the formation of the oxadiazole nucleus by microwave synthesis are considered. It is worth noting that the processes of heterofunctionalization are new in the chemistry of 1,3,4-oxadiazoles and allow us to obtain new bio-promising hybrid structures. Significant emphasis is placed on synthesized compounds with pronounced antitumor, antifungal, antituberculous, antimalarial and antibacterial activities, and structure - action dependencies. Possible modern mechanisms of action of the corresponding activity, which are inhibition of enzymes, cytotoxicity, apoptosis, etc., are analyzed in detail. Conclusions. The original works concerning the methods of synthesis of hetero derivatives of 2,5-disubstituted 1,3,4-oxadiazoles with pronounced antitumor, antifungal, antituberculous, antimalarial and antibacterial activities were generalized and systematized. The analysis of the presented material was shown the importance and real perspective of biologically oriented synthesis of drugs in this segment of the chemistry of nitrogen-containing heterocycles.